2014
DOI: 10.2478/s13380-014-0204-z
|View full text |Cite
|
Sign up to set email alerts
|

Theta power and coherence illustrate cerebral processing of octave illusion

Abstract: Background: Understanding how cerebral regions are synchronized when hearing illusions might help to explain some of the mechanisms of hallucination in psychiatric disorders. EEG theta coherence in response to the octave illusion in healthy volunteers might be used for this purpose. Methods: Right-handed healthy volunteers were invited to hear silence, normal and reversed sequences of the octave illusion. Results: After hearing both normal and reversed sequences of the octave illusion, 11 people reported heari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 56 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Documents have shown that the theta band is induced via the limbic-hippocampal-cortical feedback loop and is auditory specific [25,26,27]. Although other frequency bands exist, such as gamma rhythm, which is related to the GABA/glutamate interplay, our previous results [28] have demonstrated that the low-frequency theta band is specific to octave illusion response. Moreover, the theta band often acts as a windowing mechanism which determines the threshold and polarity of synaptic modifications [29] and is associated with positive symptoms of schizophrenia [30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Documents have shown that the theta band is induced via the limbic-hippocampal-cortical feedback loop and is auditory specific [25,26,27]. Although other frequency bands exist, such as gamma rhythm, which is related to the GABA/glutamate interplay, our previous results [28] have demonstrated that the low-frequency theta band is specific to octave illusion response. Moreover, the theta band often acts as a windowing mechanism which determines the threshold and polarity of synaptic modifications [29] and is associated with positive symptoms of schizophrenia [30].…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous neuroanatomic and neurophysiologic results [48,49], as well as our previous research with healthy participants [28], we selected a set of electrodes of interest and computed the coherence based on the EEG powers obtained in the following electrodes: Fc1, Fc2, T7, T8, Cp5, Cp6, Cp1, Cp2, P3, and P4. In order to gain the intra- and interhemispheric coherence, we excluded the midline and mastoid electrodes from further analysis, as suggested by Dien [50].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation